2016
DOI: 10.1016/j.joen.2015.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Protective Role of Regulatory T Cells in Experimental Periapical Lesion Development and Their Chemoattraction Manipulation as a Therapeutic Tool

Abstract: Introduction The pathogenesis of periapical lesions is determined by the balance between host pro-inflammatory immune response and counteracting anti-inflammatory and reparative responses, which include regulatory T cells (Tregs) as potential immunoregulatory agents. In this study, we investigated (in a cause-and-effect manner) the involvement of CCL22-CCR4 axis in Tregs migration to the periapical area and the role of Tregs in the determination of outcomes in periapical lesions. Methods Periapical lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 35 publications
1
53
0
2
Order By: Relevance
“…Promising results show attenuation of alveolar bone resorption and inflammation, attributed to the downregulation in the expression of RORγt, IL‐17 and RANKL in Th17 lymphocytes and the upregulation of Treg response by increasing their number and increasing the expression of IL‐10 and TGF‐β1 . Conversely, other studies have reported that immunization with P. gingivalis favours the polarization of Th17 response and the subsequent alveolar bone loss by inducing the RANKL production . These conflicting results are discussed by the authors, who argue that concentration of inoculated bacteria and periodontitis induction methods that are used may modify the expected events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising results show attenuation of alveolar bone resorption and inflammation, attributed to the downregulation in the expression of RORγt, IL‐17 and RANKL in Th17 lymphocytes and the upregulation of Treg response by increasing their number and increasing the expression of IL‐10 and TGF‐β1 . Conversely, other studies have reported that immunization with P. gingivalis favours the polarization of Th17 response and the subsequent alveolar bone loss by inducing the RANKL production . These conflicting results are discussed by the authors, who argue that concentration of inoculated bacteria and periodontitis induction methods that are used may modify the expected events.…”
Section: Discussionmentioning
confidence: 99%
“…12,31 Conversely, other studies have reported that immunization with P. gingivalis favours the polarization of Th17 response and the subsequent alveolar bone loss by inducing the RANKL production. 26,32 These conflicting results are discussed by the authors, 12,33 who argue that concentration of inoculated bacteria and periodontitis induction methods that are used may modify the expected events. For instance, subcutaneous injection with formalin-killed bacteria could have a protective effect in comparison with using live bacteria.…”
Section: Interventions For Immuno-modulation Targeting Tregsmentioning
confidence: 99%
“…The increased bone destruction in IL-17-deficient animals was correlated with the elevated number of osteoclasts and increased expressions of the bone-resorptive cytokines, IL-1 and MIP-2, in PLs (AlShwaimi et al 2013). In the study by Francisconi et al (2016), experimental PLs in C57Bl/6 mice were induced by pulp exposure and bacterial inoculation. The development of lesions was similar to what was observed in the aforementioned studies, and inhibition of Treg function by anti-GITR or CCR4 depletion resulted in a significant increase in PL severity and lesion evolution rate, associated with the upregulation of proinflammatory, Th1, Th17 and tissue-/bone-destructive markers (IL-1b, IL-17, TNF-a, IFN-c, MMP-2 and RANKL) and downregulation of Tregs and healing markers (Francisconi et al 2016).…”
Section: Animal Studiesmentioning
confidence: 99%
“…1 Leukocytes are recruited from the periapical tissues in response to intracanal bacterial infection, and the persistence of the antigenic stimulus can result in chronic periapical lesions such as periapical granuloma and radicular cyst. 2 The role of immunological mechanisms in the pathogenesis of periapical lesions has been widely documented. 3 The interplay between immune regulatory mechanisms and effector T cell responses is a crucial Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript.…”
Section: Introductionmentioning
confidence: 99%